Detecting voltage shifts and charge storage anomalies by iron nanoparticles in three-electrode cells based on converted iron oxide and lithium iron phosphate. (1st February 2023) - Valvo, Mario; Chien, Yu-Chuan; Liivat, Anti; Tai, Cheuk-Wai
Highlights: Voltage shifts due to reduced sizes of Fe nanoparticles are accurately detected. A dedicated F-free three-electrode cell enables a systematic study of these shifts. An in-depth analysis confirms a strong pseudo-capacitive charge storage for Fe/Li2 O. A peculiar tendency to early oxidation of the smallest Fe nanoparticles is observed. Abstract: Noticeable voltage shifts have been observed in the charge/discharge profiles of a three-electrode cell with a lithium metal reference electrode and having a deeply lithiated iron oxide (Fe/Li2 O) negative electrode galvanostatically cycled in a limited potential range against a positive LiFePO4 counterpart. The origin of such shifts has been attributed to charge storage anomalies in the Fe/Li2 O nanocomposite due to characteristic reduced Fe nanoparticle sizes. These shifts also affected the extreme points of the voltage profiles of the positive electrode, which was also independently monitored. A combined evaluation of voltage profile slippages with possible changes in internal resistance and/or Li + inventory loss, including an aimed analysis of current interruptions at the end of each lithiation/de-lithiation half-cycle to monitor the internal resistance and diffusion resistance coefficient of the Fe/Li2 O electrode, has enabled a clarification of its altered charge storage. An asymmetric behaviour of the Fe/Li2 O electrode during Li + uptake/release has been revealed, highlighting a progressive, diffusion-controlled-type voltage drift at low potentials vs. Li + /Li, and an unusual tendency to slight oxidation with capacitive variations during the reverse electrochemical processes at higher voltages, instead. Graphical abstract: Image, graphical abstract